Novel B19-like parvovirus in the brain of a harbor seal. - Rogier Bodewes; Ana Rubio García; Lidewij C M Wiersma; Sarah Getu; Martijn Beukers; Claudia M E Schapendonk; Peter R W A van Run; Marco W G van de Bildt; Marjolein J Poen; Nynke Osinga; Guillermo J Sánchez Contreras; Thijs Kuiken; et al. (PLoS ONE, 2013)
Using random PCR in combination with next-generation sequencing, a novel parvovirus was detected in the brain of a young harbor seal (Phoca vitulina) with chronic non-suppurative meningo-encephalitis that was rehabilitated at the Seal Rehabilitation and Research Centre (SRRC) in the Netherlands. In addition, two novel viruses belonging to the family Anelloviridae were detected in the lungs of this animal. Phylogenetic analysis of the coding sequence of the novel parvovirus, tentatively called Seal parvovirus, indicated that this virus belonged to the genus Erythrovirus, to which human parvovirus B19 also belongs. Although no other seals with similar signs were rehabilitated in SRRC in recent years, a prevalence study of tissues of seals from the same area collected in the period 2008-2012 indicated that the Seal parvovirus has circulated in the harbor seal population at least since 2008. The presence of the Seal parvovirus in the brain was confirmed by real-time PCR and in vitro replication. Using in situ hybridization, we showed for the first time that a parvovirus of the genus Erythrovirus was present in the Virchow-Robin space and in cerebral parenchyma adjacent to the meninges. These findings showed that a parvovirus of the genus Erythrovirus can be involved in central nervous system infection and inflammation, as has also been suspected but not proven for human parvovirus B19 infection.